Decreasing the Negative Effects of Work-Related Stress in Unchanged Working Environments - Stauder, Adrienn; Cserháti, Zoltán; Konkolÿ Thege, Barna (European Journal of Mental Health, 2018)
Background: Chronic work-related stress has a negative impact on both physical and mental health. The present translational study’s goal was to investigate the effectiveness of an individual-focused, standardised coping skills training provided outside the employment setting.Methods: 89 working individuals (76 women, 13 men; mean age: 41.3 years) from diverse occupational backgrounds completed a 12-hour stress management program. Work stress and overcommitment were measured by the Effort-Reward Imbalance Questionnaire (ERI). Outcome variables included perceived stress (PSS10), anxiety- (STAI-T), depressive- (BDI), and subjective somatic symptoms (PHQ15), as well as well-being (WHO-WB5), life meaning (BSCI-LM), coping skills (LSS), and overall life satisfaction.Results: The post-intervention scores showed no change in work-related stress or overcommitment, whilst coping skills improved. Further, anxiety-, depression- and somatic symptoms decreased significantly and there was a significant increase in well-being, life meaning, and life satisfaction scores. These improvements were observed mostly in the subgroup reporting higher initial levels of work stress, associated with higher symptom scores. In the low-stress subgroup, only coping skills, perceived stress, and life meaning scores improved.Conclusions: A short, well-structured multimodal coping skills training can significantly reduce overall stress level and stress-related symptoms, and improve well-being and satisfaction in employees suffering from high work stress even if the work environment remains unchanged.